2005
DOI: 10.1111/j.1467-9353.2005.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of Ethanol Plants on Local Grain Prices

Abstract: A considerable number of farmer-owned ethanol plants have been built in the past few years, with many more planned. In part, farmers' investment in ethanol plants is an attempt to increase grain prices in their local market. We examined this issue by estimating the impact on local grain prices of twelve ethanol plants that opened from 2001 to 2002. We find that these new ethanol plants increased local grain prices, but the impact was not uniform around the plant. Markets downstream from a new plant, where pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 6 publications
7
71
0
Order By: Relevance
“…For over 40 years, corn grain has been the most cost effective and readily available energy source used by beef producers in the U.S., but, at times, competition from the ethanol industry results in an unprecedented increase in feed costs (McNew and Griffith, 2005). Previous approaches to reduce ration costs have focused on increasing dietary inclusions of alternative feeds, such as DDGS, forages, or other fiber-based by-products in finishing (greater than 450 kg) cattle diets (Ham et al, 1994;Klopfenstein et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For over 40 years, corn grain has been the most cost effective and readily available energy source used by beef producers in the U.S., but, at times, competition from the ethanol industry results in an unprecedented increase in feed costs (McNew and Griffith, 2005). Previous approaches to reduce ration costs have focused on increasing dietary inclusions of alternative feeds, such as DDGS, forages, or other fiber-based by-products in finishing (greater than 450 kg) cattle diets (Ham et al, 1994;Klopfenstein et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The empirical debate centers on the degree or extent to which the increase in demand drives up corn prices. A study examining the introduction and growth of ethanol plants in the U.S. between 2001 and 2004 concluded there was a direct impact on ethanol demand and corn prices (McNew & Duane, 2005). One independent researcher in Canada concluded that 37 % of the rise in corn prices can be attributed to the increased use of corn for ethanol production (Kowal, 2008).…”
Section: The Demand For Ethanol and Corn Pricesmentioning
confidence: 99%
“…The regulation of pharmaceuticals by the Food and Drug Administration slowed down the introduction of new drugs and may, on net, have caused more unnecessary death and suffering than it prevented (Gieringer 1985;Higgs 1995;Kazmin 1990;Klein 2000). Subsidies and regulatory measures aimed at encouraging the use of alternative sources of energy resulted in higher prices for American corn, which was diverted from world markets into ethanol production (McNew and Griffith 2005). This, in turn, may have had the effect of harming the poor in less developed countries.…”
Section: Is the Illusion Of Explanatory Depth Important?mentioning
confidence: 99%